2002
DOI: 10.1271/bbb.66.840
|View full text |Cite
|
Sign up to set email alerts
|

The Biological and Structural Similarity between Lunularic Acid and Abscisic Acid

Abstract: Lunularic acid (LA) inhibited not only the germination and the growth of cress and lettuce at 1 mM but also the gibberellic acid (GA3)-induced alpha-amylase induction in embryoless barley seeds at 120 microM, which was recognized as a specific activity of abscisic acid (ABA). Moreover LA and ABA equally inhibited the growth of Lunularia cruciata A18 strain callus at 40 and 120 microM. A computational analysis revealed that the stable conformers of LA could be superimposed on the stable ABA conformers. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…We previously reported that the induction of a-amylase by 5ϫ10 Ϫ8 M GA 3 was inhibited by 1.1ϫ10 Ϫ5 M and 3.3ϫ10 Ϫ5 M of ABA application by 98% and 100%, respectively, using the Somogyi-Nelson method. 5) These results were almost the same as in this experiment. Consequently, it can be deemed that the new method has almost equal detectability as that of the Somogyi-Nelson method.…”
Section: ϫ7supporting
confidence: 84%
See 1 more Smart Citation
“…We previously reported that the induction of a-amylase by 5ϫ10 Ϫ8 M GA 3 was inhibited by 1.1ϫ10 Ϫ5 M and 3.3ϫ10 Ϫ5 M of ABA application by 98% and 100%, respectively, using the Somogyi-Nelson method. 5) These results were almost the same as in this experiment. Consequently, it can be deemed that the new method has almost equal detectability as that of the Somogyi-Nelson method.…”
Section: ϫ7supporting
confidence: 84%
“…4,5) Although the method has excellent sensitivity for reducing sugars, wastewater including arsenic and copper compounds arises in the experimental procedure. 6) In 1998, Satoyama et al reported a convenient method for measuring a-amylase activity.…”
Section: Introductionmentioning
confidence: 99%
“…LNA inhibited growth of gemmae of liverworts and germinating seeds of both monocot and dicot species Nakayama et al 1996). In addition, LNA inhibited GAinduced a-amylase production in the embryoless seeds of barley (Yoshikawa et al 2002). LNA was found to be distributed in a wide variety of liverwort species and various classes of algae, but it was not detected in mosses or most pteridophytes and angiosperms (Pryce 1972).…”
Section: Bryophytes and Abamentioning
confidence: 97%
“…This confusion was due to (1) unsuccessful detection of endogenous ABA in liverwort species (Pryce 1971;Weiler 1979) and (2) the fact that liverworts accumulate a substantial amount of lunularic acid (LNA) (Valio et al 1969;Yoshikawa et al 2002). LNA was first identified from Lunularia cruciata as a growth inhibitory substance that accumulates in association with its photoperioddependent dormancy (Valio et al 1969).…”
Section: Bryophytes and Abamentioning
confidence: 99%
See 1 more Smart Citation